A majority of Ig H chain cDNA of normal human adult blood lymphocytes resembles cDNA for fetal Ig and natural autoantibodies - Huang, C; Stollar, BD (The Journal of immunology (1950), 1993)
Certain Ig VH gene segments, with few or no mutations, recur frequently in natural autoantibodies, fetal antibodies, and products of B cell tumors. The goal of this study was to determine whether similar Ig gene segment usage occurs in normal human adult PBL. Extending previous analyses, 105 randomly picked H chain V region clones of representative cDNA libraries from PBL were sequenced. Clones were from: IgM and IgG libraries from one RNA sample of a normal adult; a second IgM library from the same subject 11 mo later; and one IgM library from a second subject. Although some clones had clear evidence of mutation, 48 of 77 IgM clones (62%) shared 99% or more identity with known germline VH segments, and most of these had no mutations in the CDR3 portion of the JH segment. Certain VH gene segments, expressed in autoantibodies and fetal antibodies, occurred at high frequency in these libraries. Fourteen of the clones with 99% identity to known VH segments had CDR3 segments identical to portions of known germline DH gene sequences; two such clones had no N nucleotides at the VHDH or DHJH junctions. IgG-encoding sequences had more mutations than IgM-encoding sequences. JH and DH usage was not random. The circulating B cell population may represent a distinct compartment, with a large proportion of cells similar to those of the fetal and natural autoantibody repertoire. Polyreactive Ig products of these circulating cells may serve a screening function, binding and delivering diverse Ag to secondary lymphoid tissues where more highly selective antibodies are formed to foreign or self-Ag.